The issue of workplace stress: a case study in forensic division, Department of Chemistry, Malaysia / Mohamad Arif Mohamad Rastari and Yun Farha Jasin - Mohamad Rastari, Mohamad Arif; Jasin, Yun Farha (Faculty of Administrative Science and Policy Studies, 2012)
Stress occurs in a wide range of work circumstances but is often made worse when employees feel they have little support from supervisors and colleagues and where they have little control over work or how they can cope with its demands and pressures. Therefore, this study attempts to address the issue of stress in organization, mainly in Forensic Division, Department of Chemistry, Malaysia. In addressing the issue of stress, this study will examine the factors that contribute towards stress among the workers in the organization. This study will only focus on five factors of stress that are interpersonal factors, workload factors, role-conflict factors, role ambiguity and organizational and physical factors. The objectives of this research is to assess whether these 5 factors contribute towards stress in the Forensic Division and to identify which factor that contribute the most towards stress. Out of 140 workers of the Forensic Division, 103 workers have been selected through simple random sampling method to answer the questionnaire provided. The questionnaire is used to asses which factor that contribute towards stress and the behavioural symptoms of stress among the workers in the Division. This research was conducted from March to May 2012.